Pelatihan Ecoprint sebagai Pemberdayaan Ekonomi Kreatif bagi calon Pengusaha dengan Pendekatan ABCD models: Pelatihan Ecoprint sebagai Pemberdayaan Ekonomi Kreatif bagi calon Pengusaha - Yuyun Maryuningsih; Novianti Muspiroh; Siti Sholeha; Annis Maemunah; Rizki Sukma Wijaya (Jurnal Indonesia Mengabdi, 2021)
This service is carried out with ecoprint training for young Cirebon entrepreneurs with the aim of empowering the creative economy for potential entrepreneurs. Cirebon has natural wealth as an asset that can be used as ecoprint material. The ecoprint training was carried out by providing materials and practices for making ecoprints, both founding techniques and steam techniques. The training will be held for two months in 2021 for the community of young aspiring entrepreneurs. The training products produced are in the form of hijabs, t-shirts, tote bags and shirts. The responses of the participants of the ecoprint training stated that they were quite interested in developing an ecoprint business.